Plan de negocios para la implementación de una cafetería móvil en la ciudad de Guayaquil - Villacis Delgado, Evelyn Paola (2009)
We though in this Project due to in this times most of the people from 20 years old have a very accelerate style of life so they have to do several activities and often they do not have time to prepare at their homes their breakfast or any aperitif that complements their meals, some of them choose to not have breakfast so they take the risk of get any digestive sickness, because of this we decide to create CoffyPan , which is about to offer a fast service Cafeteria through a vehicle complete modify to place the cafeteria inside itself so it can be move to different strategic points inside the city of Guayaquil during the day and night. Among the benefits that customers can get when they buy our products or service are: Excellent quality of breakfast and efficient service, near of the place of working and Breakfast to the office service. Once we made the financial analysis of the CoffyPan Business Plan in the city of Guayaquil, it was determined that the initial investment is $44886,52 so we conclude this project is suitable with NPV $5074,70 and IRR 16,64% in a recovery period of 4 years.